Meningkatkan resiliensi matematis mahasiswa pada mata kuliah matematika dasar melalui pendekatan differentiated instruction - Fatimah, Ade Evi; Purba, Azrina (Mahesa Research Center, 2021)
This study is a Classroom Action Research with a qualitative descriptive method, which aims to increase students' mathematical resilience when using the Different Instruction approach. The subjects of this study were 40 first-semester students of class B of Informatics Engineering and Computer Education STKIP Al Maksum Langkat. The object of this research is the students' mathematical resilience ability through the Different Instruction approach in the basic mathematics subject matter of functions. This research procedure refers to four stages, namely planning, acting, observing, and reflecting. This research was conducted in two cycles, the research was based on the criteria that reached 85% for students who produced a minimum result of 65%. The instrument used in this study was a non-test question in the form of a mathematical resilience scale given at the beginning and end of the lesson. Based on the results of the study, it can be ignored that the Instruction Differentiation approach can improve the mathematical resilience of the first semester B grade students of the PTIK study program, by grouping students based on learning styles more effective in increasing students' mathematical resilience in applying the Instruction Differentiation approach.